2015
DOI: 10.1055/s-0034-1391304
|View full text |Cite
|
Sign up to set email alerts
|

Self-expandable metallic stents vs. plastic stents for endoscopic biliary drainage in hepatocellular carcinoma

Abstract: SEMSs were not superior to plastic stents for the palliation of malignant biliary obstruction in HCC with regard to successful drainage, stent patency, and adverse events. Patient survival was better in the plastic stent group. Given the lower cost, plastic stents could be a favorable option for malignant biliary obstruction caused by HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 18 publications
0
23
1
Order By: Relevance
“…Previous studies of the effects of biliary drainage in HCC patients with obstructive jaundice have shown that median survival was about 1.3-1.5 months in patients with ineffective drainage and about 4.9-8.7 months in patients with effective drainage [2,4,6,8]. Median survival was further prolonged, to about 8-13.4 months, in patients with effective drainage who received HCC treatment [14][15][16].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous studies of the effects of biliary drainage in HCC patients with obstructive jaundice have shown that median survival was about 1.3-1.5 months in patients with ineffective drainage and about 4.9-8.7 months in patients with effective drainage [2,4,6,8]. Median survival was further prolonged, to about 8-13.4 months, in patients with effective drainage who received HCC treatment [14][15][16].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, palliative biliary drainage would increase the possibility of these patients receiving additional treatment for HCC and prolong their survival [6]. Effective drainage is important in the management of HCC accompanied by obstructive jaundice [1][2][3][4][5][6][7][8]. In these studies, IHD dilatation was an indicator of obstruction in most patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A hepatocellular carcinoma (HCC) rarely expands into the biliary tract; the incidence is 1.2 to 9.0% according to previous reports [1,2]. In this situation, because of its hypervascular nature, cholangitis or hemobilia may be sometimes complicated [3]. Hemobilia due to HCC can usually be treated by transarterial chemoembolization or radiofrequency treatment [4].…”
Section: Introductionmentioning
confidence: 99%